The impact of internal audit on improving the efficiency of the financial performance of government units: a case study on King Abdulaziz University in Jeddah - Abdulrahman, Najla Ibrahim; Banasser, Lamis Jamel (Journal of Economic, Administrative and Legal Sciences, 2022)
The study dealt with the impact of internal auditing on improving the efficiency of the financial performance of government units, as applied to King Abdulaziz University in Jeddah. It aimed to know the impact of the independence of the internal auditor on improving the efficiency of financial performance, and to know the impact of the professional competence of the internal auditor on improving the efficiency of financial performance, and to know the impact of the internal organization of the internal audit department on improving the efficiency of the financial performance of government units. To the descriptive survey method for a random sample of the financial and administrative staff at King Abdulaziz University in Jeddah, where the questionnaire was distributed to the study sample and the results were analyzed using appropriate statistical methods. The two researchers reached a set of results, the most important of which are the following: The internal auditor’s enjoyment of independence, honesty, objectivity and impartiality contributes greatly to improving the efficiency of financial performance, and the internal auditor’s enjoyment of ethical values ​​contributes to increasing the efficiency of internal auditing and thus improving the efficiency of financial performance in government units. Accordingly, the two researchers recommended the need for a legal obligation for internal auditors to abide by internal auditing standards and to adhere to the rules of professional conduct because they represent an important cornerstone of internal auditing in government units.